Revealing The Accountability of Nurul Haromain Islamic Boarding Schools: A Phenomenological Study - Rodliyah, Siti; Djamhuri, Ali; Prihatiningtias, Yeney Widya (Jurnal Ilmiah Akuntansi dan Bisnis, 2021)
The objective of this study is to reveal the sense of accountability at Nurul Haromain Islamic boarding school. Qualitative method and interpretive paradigm were used to understand and explain the accountability practice phenome, and phenomenological approach was used to reveal the sense of accountability based on the experience of individuals, in this case the administrators of the school. This study finds that the sense of accountability is very contextual depending on the space and time as well as individuals who sense it. For the school administrators, accountability is practiced upon the amanah (mandate) that the school should serve as a  dakwah  institution and the manager of community’s fund in the form of community services and proper financial management. The implication of such accountability is ensured by their faith quality and the enforcement of ethics and morality by human resource seasoned in Islamic boarding school environment. Keywords: accountability, mandate, phenomenology, Islamic boarding school